1992
DOI: 10.1111/j.1476-5381.1992.tb14246.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent and ‐independent effects of exogenous ATP, adenosine, GTP and guanosine on vascular tone and cyclic nucleotide accumulation of rat mesenteric artery

Abstract: 1 The effects of exogenous guanosine 5'-triphosphate (GTP) and guanosine on vascular tone and cyclic nucleotide accumulation of noradrenaline-precontracted endothelium-intact and endothelium-denuded rat mesenteric artery rings were compared with the effects of the known purinoceptor agonists adenosine 5'-triphosphate (ATP) and adenosine.2 GTP (10pM-1 mM) dose-dependently relaxed endothelium-intact mesenteric artery rings by producing a rapid initial response followed by sustained relaxation resembling the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…In this vessel, ATP acts on purinergic receptors on smooth muscle to produce contraction via P2X receptors and additionally endothelium-independent relaxation via P2Y receptors (Mathieson and Burnstock, 1985;Burnstock and Warland, 1987b). Striking evidence for species differences between rabbit and rat mesenteric arterial purinergic signaling was presented in later studies, with the observation that ATP relaxation of rat mesenteric arteries was elicited largely via the endothelium (Vuorinen et al, 1992). Similarly, hyperpolarizations to ATP in hamster mesenteric arteries were endothelium dependent (Thapaliya et al, 1999), as were relaxations to ATP, ADP, and UTP in the hamster mesenteric arterial bed (Ralevic and Burnstock, 1996b).…”
Section: Mesenteric Vesselsmentioning
confidence: 86%
“…In this vessel, ATP acts on purinergic receptors on smooth muscle to produce contraction via P2X receptors and additionally endothelium-independent relaxation via P2Y receptors (Mathieson and Burnstock, 1985;Burnstock and Warland, 1987b). Striking evidence for species differences between rabbit and rat mesenteric arterial purinergic signaling was presented in later studies, with the observation that ATP relaxation of rat mesenteric arteries was elicited largely via the endothelium (Vuorinen et al, 1992). Similarly, hyperpolarizations to ATP in hamster mesenteric arteries were endothelium dependent (Thapaliya et al, 1999), as were relaxations to ATP, ADP, and UTP in the hamster mesenteric arterial bed (Ralevic and Burnstock, 1996b).…”
Section: Mesenteric Vesselsmentioning
confidence: 86%
“…Few in vitro studies have already shown that ATP exerts vasodilation partially via endothelium independent mechanisms (Mathieson & Burnstock, 1985;Vuorinen et al, 1992;McMillan et al, 1999). Vascular smooth muscle cells express P2y receptors which may mediate vasodilation (Wang et al, 2002).…”
Section: Why Was Atp-induced Vasodilation Not Inhibited By Any Of Thementioning
confidence: 99%
“…Its vascular actions are not restricted to the coronary circulation since it causes vasodilatation in most vascular beds, although vasoconstriction may also occur in the kidney (Rossi et al, 1987). Vuorinen et al (1992Vuorinen et al ( , 1994 recently reported that rat mesenteric artery rings were relaxed by adenosine and that this action was blocked by the non-selective Al and A2 receptor antagonist, 8-phenyltheophylline (8-PT). Removal of the endothelium in these rings slightly attenuated the action of adenosine.…”
Section: Introductionmentioning
confidence: 99%